Managing flash flood crises with cultural perspectives: A user-centric feature identification study - Siti Fatimah Abdul Razak; Sumendra Yogarayan; Umar Ali Bukar; Md. Shohel Sayeed (PLoS ONE, 2025)
Flash floods are severe disaster that have caused enormous damage to people, property, and the environment. Despite the conventional emphasis on technical and engineering solutions in controlling flash flood disasters, this study investigates the understudied issue of user-centric cultural viewpoints, inspired by Grid-Group Cultural Theory, and their potential impact on crisis management. The study collected 351 responses, primarily targeting adults in flood-prone areas using convenience sampling method with the goal of exploring cultural bias for feature identification of in-vehicle flash flood app. Accordingly, the research investigates the participants responses using quantitative approach which includes descriptive statistics, exploratory factor analysis, average factor, and rank scoring analysis to uncover critical user-centric cultural traits that might improve preparedness, response, and recovery activities during flash flood disasters. The findings of the study identified distinct cultural biases that impact perceptions and preferences regarding features of an in-vehicle flash flood app. By integrating Grid-Group Cultural Theory as a framework for analysis, the study highlights the importance of incorporating diverse cultural perspectives into flash flood management strategies. The result emphasizes the need to apply a holistic approach that integrates people’s knowledge and practices with technical solutions. Recommendations of features for future development of in-vehicle flash flood app is provided based on each cultural bias aligned with the theory to build more resilient communities in the face of flash flood occurrences.